The screening of congenital heart disease by cardiac auscultation and 12-lead electrocardiogram among Indonesian elementary school students. (14th February 2021) - Dinarti, Lucia K.; Murni, Indah K.; Anggrahini, Dyah W.; Dewanto, Vera C.; Pritazahra, Armalya; Hadwiono, Muhammad R.; Fajarwati, Prahesti; Hartopo, Anggoro B.
Abstract: Background: Screening for congenital heart disease (CHD) in school students is well-established in high-income countries; however, data from low-to-middle-income countries including Indonesia are limited. Aim: This study aimed to evaluate CHD screening methods by cardiac auscultation and 12-lead electrocardiogram to obtain the prevalence of CHD, confirmed by transthoracic echocardiography, among Indonesian school students. Methods: We conducted a screening programme in elementary school students in the Province of Special Region of Yogyakarta, Indonesia. The CHD screening was integrated into the annual health screening. The trained general practitioners and nurses participated in the screening. The primary screening was by cardiac auscultation and 12-lead electrocardiogram. The secondary screening was by transthoracic echocardiography performed on school students with abnormal findings in the primary screening. Results: A total of 6116 school students were screened within a 2-year period. As many as 329 (5.38%) school students were detected with abnormalities. Of those, 278 students (84.49%) had an abnormal electrocardiogram, 45 students (13.68%) had heart murmurs, and 6 students (1.82%) had both abnormalities. The primary screening programme was successfully implemented. The secondary screening was accomplished for 260 school students, and 18 students (6.9%) had heart abnormalities with 7 (2.7%) who were confirmed with septal defects and 11 (4.2%) had valve abnormalities. The overall prevalence was 0.29% (18 out of 6116). Conclusions: The primary screening by cardiac auscultation and 12-lead electrocardiogram was feasible and yielded 5.38% of elementary school students who were suspected with CHD. The secondary screening resulted in 6.9% confirmed cardiac abnormalities. The cardiac abnormality prevalence was 0.29%.